The Effect of NPL, BI Rate, Inflation, NIM, and CAR on the ROA of Commercial Banks in Indonesia During 2019–2023 - Michelle Priscilla Gunawan; Surya Dewi Rustariyuni (Digital Innovation : International Journal of Management, 2025)
Profitability, measured by Return on Asset (ROA), is a key indicator for assessing the performance and resilience of the banking sector. During the 2019–2023 period, the Indonesian banking sector faced significant pressure from the COVID-19 pandemic, which impacted asset quality and financial performance. This study aims to analyze the simultaneous and partial effects of Non-Performing Loan (NPL), the BI Rate, inflation, Net Interest Margin (NIM), and Capital Adequacy Ratio (CAR) on the ROA of commercial banks in Indonesia. This research employs a quantitative approach using monthly secondary data from 2019 to 2023. The analysis was conducted using Robust Least Squares (RLS) with M-estimation, a Wald test for simultaneous significance, and a z-statistic for partial tests. The results indicate that, simultaneously, the five independent variables have a significant effect on ROA with a significance value of 0,000 and a coefficient of determination of 67,1 percent. Partially, NPL has a significant negative effect on ROA, while NIM, CAR, and inflation have significant positive effects. The BI Rate shows no significant influence. The implications of these findings highlight the managerial importance of strengthening credit risk management to control NPL, enhancing intermediation efficiency to maintain a healthy NIM, and preserving capital adequacy. From a policy perspective, these results justify the continued strengthening of prudential supervision over banks' internal ratios by financial authorities. Furthermore, the insignificance of the BI Rate suggests that the monetary policy transmission to bank profitability is indirect, necessitating a focus on internal factors to maintain the stability of the banking sector.